Historical Wood: Structure, Properties and Conservation - Broda, Magdalena; Hill, Callum (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is a selection of manuscripts devoted to the conservation and preservation of wooden cultural heritage. The articles present the new methods for conservation of various historical wooden artefacts, reliable modern techniques for characterisation of the wood structure, properties and degree of degradation, and discusses problems and doubts related to all aspects of conservation and re-conservation of wooden cultural heritage. It contains both review and research papers to give the readers a broader picture of the problems and issues related to the conservation of wooden historical objects and structures. We need to remember that wooden cultural heritage is an integral part of our culture and history that define our humanity. We are obliged to protect it, save it from oblivion, and preserve it for future generations.